PROBLEMS OF TRANSLATION: LINGUISTIC, SEMANTIC, AND CULTURAL PERSPECTIVES (Ideal Journal of Multidisciplinary Research, 2026)
Translation is a multifaceted process that involves transferring meaning, style, and cultural nuances from one language to another. Translators face numerous challenges, including linguistic differences, semantic ambiguities, idiomatic expressions, cultural references, and stylistic features. This article examines the main problems encountered in translation, with a particular focus on English–Uzbek and Uzbek–English translation. The study discusses linguistic, semantic, and cultural difficulties and explores strategies for overcoming them. Comparative examples, including idioms, metaphors, proverbs, and stylistic devices, demonstrate how translators balance meaning, style, and cultural relevance. Understanding these challenges is essential for translators, linguists, and language learners to ensure effective and accurate communication across languages.
Keywords: Translation, linguistic equivalence, cultural transfer, idioms, semantics, stylistics, English–Uzbek translation, metaphor translation.